Canadian contributions to forest insect pathology and to the use of pathogens in forest pest management. (25th June 2015) - van Frankenhuyzen, Kees; Lucarotti, Christopher; Lavallée, Robert
Abstract: The study of insect pathogens became established as a distinct discipline in the late 1940s. In the ~65 years that followed, forest pest management was the main theatre for the development and practice of insect pathology in Canada. Researchers from the federal government and academic institutions contributed to the growing discipline by acquiring foundational knowledge on taxonomy, mode of action, natural occurrence, and ecological role of key pathogens infecting forest pest insects, covering an array of fungi, Microsporidia, viruses, and bacteria. The ultimate goal was to develop pathogen-based alternatives to synthetic insecticides used in large-scale forest protection programmes throughout eastern Canada. That goal was achieved through the development of baculovirus-based products for control of gypsy moths (Lepidoptera: Erebidae), tussock moths (Lepidoptera: Erebidae), and various sawfly (Hymenoptera) species, which are now in the hands of private industry and poised for growing operational use. The second success was the development of products based on Bacillus thuringiensis Berliner (Bacillaceae), which have almost entirely replaced synthetic insecticides in forest protection. We review those successes and other key Canadian contributions to forest insect pathology within the context of emerging digital, molecular, and other technologies, and show how they have altered today's face of forest pest management in Canada.